Avaliação in vitro da citotoxidade e genotoxidade celular do cimento de ionômero de vidro modificado por carbonato de cálcio - Giacomelli, Édio (2017)
The aim of this study was to evaluate the biocompatibility of conventional glass ionomer cement (GIC) modified by calcium carbonate by means of cytotoxicity and genotoxicity tests. The calcium carbonate (CC), in proportions of 1%, 5% and 10%, was added to the GIC powder. A polytetrafluoroethylene matrix (10 mm diameter and 3 mm height) was used to make the samples, and four groups were obtained (n = 4): G1 – only GIC (control); G2 – GIC with 1% CC; G3 – GIC with 5% CC; G4 – GIC with 10% CC. The preparation of the samples was carried out in accordance with ISO 10993-12. The MTT test was used to evaluate the cell cytotoxicity, and the micronucleus and comet tests were performed to evaluate the genotoxicity, by using a mouse fibroblast cell culture of the NIH/3T3 lineage. According to MTT test, the samples with 1% and 5% CC showed a higher cytotoxic potential, and the samples with 10% CC presented a cellular viability index comparable to the GIC. The micronucleus test showed that GIC with 10% CC produced an improvement in cell proliferative potential (IPBC).CIV with 5% CC had a reduction in IPBC that did not compromise the material from the genotoxic point of view. In the comet test, groups with the addition of CC had a small increase in genotoxic potential compared with GIC. It was concluded that the addition of 10% CC to the GIC had a low cytotoxic potential and it is feasible for use in the cellular environment, and the addition of 1%, 5% and 10% CC to the GIC did not induce genetic damage.